12.6k views
0 votes
Solve for x : ax+v=3(x-c)

User CBono
by
5.5k points

1 Answer

7 votes

Answer:


x=(-3c-v)/(a-3);\quad \:a\\e \:3

Explanation:

--expand--

ax+v=3x-3c

--subtract v from each side--

ax+v-v=3x-3c-v

--simplfy--

ax=3x-3c-v

--subtract 3x from both side--

ax-3x=3x-3c-v-3x

--simplfiy--

--factor--(factor out the x from ax-3)


x\left(a-3\right)=-3c-v


(x\left(a-3\right))/(a-3)=-(3c)/(a-3)-(v)/(a-3);\quad \:a\\e \:3


x=(-3c-v)/(a-3);\quad \:a\\e \:3

<3

Red

User Sergio Pardo
by
4.6k points